Proceedings, Annual General Meeting, 1991 (The Southern African Institute of Mining and Metallurgy, 1991)
The 94th Annual General Meeting of The South Mrican Institute of Mining and metallurgy was held in the Gold Room of the Transvaal Automobile Club in Johannesburg on Wednesday, 14th August, 1991. Obituaries The President announced the deaths of the following members of the Institute: Honorary Life Fellow and Past President